2005
DOI: 10.4049/jimmunol.174.12.8135
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Plasminogen Activator Inhibitor-1-Deficient Mice from Nasal Allergy

Abstract: This study was performed to clarify the relationship between fibrinolytic components and the pathology of allergy, particularly that during the development of nasal allergy and nasal tissue changes. Intranasal OVA challenge after sensitization by i.p. administration of OVA induced a higher level of excess subepithelial collagen deposition in wild-type (WT) C57BL/6J mice than in plasminogen activator inhibitor (PAI)-1-deficient (PAI-1−/−) mice. The excess PAI-1 induction in the nasal mucosa and higher level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…In this latter investigation, OVA-sensitized mice demonstrated increased PAI-1 levels in nasal washings upon intranasal OVA challenge; this locally produced PAI-1 contributed to a Th2 response as reflected by Th1-biased responses in sensitized PAI-1 Ϫ/Ϫ mice characterized by reduced OVA-specific circulating IgE and elevated plasma IgG2a levels, as well as lower IL-4 and IL-5 and higher IFN-␥ concentrations in nasal lavage fluid (23). Our present findings extend and are partly in line with these results: naive PAI-1 Ϫ/Ϫ mice displayed enhanced systemic IFN-␥ release after i.p.…”
Section: Discussionmentioning
confidence: 99%
“…In this latter investigation, OVA-sensitized mice demonstrated increased PAI-1 levels in nasal washings upon intranasal OVA challenge; this locally produced PAI-1 contributed to a Th2 response as reflected by Th1-biased responses in sensitized PAI-1 Ϫ/Ϫ mice characterized by reduced OVA-specific circulating IgE and elevated plasma IgG2a levels, as well as lower IL-4 and IL-5 and higher IFN-␥ concentrations in nasal lavage fluid (23). Our present findings extend and are partly in line with these results: naive PAI-1 Ϫ/Ϫ mice displayed enhanced systemic IFN-␥ release after i.p.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the Th2 response was downregulated and the immune response shifted from a Th2-dominant to a Th1-dominant reaction in PAI-1 Ϫ/Ϫ mice (30). The reduction of airway inflammation that occurs with increased fibrinolysis may be one mechanism by which the uPA/plasmin system reduces airway remodeling and fibrogenic factors such as TGF-␤.…”
Section: Discussionmentioning
confidence: 99%
“…78 PAI-1 has been implicated as a mediator of the allergic immune response: in a murine allergic rhinitis model, PAI-1-deficient mice showed a suppressed Th2 response and fewer symptoms. 85 In addition, PAI-1-deficient mice displayed a reduced airway hyper-responsiveness in the ovalbumin-induced allergic lung inflammation model. 82 In a model of chronic asthma produced by exposure to aerosolized ovalbumin during 4 weeks, PAI-1 deficiency did not influence peribronchial eosinophilic infiltration, goblet cell hyperplasia, or ovalbumin-specific IgE levels.…”
Section: Fibrinolysis In Asthmamentioning
confidence: 99%